Practice and Application of Marketing in the Chain Stores of Sanya Photo Studios - Qiao, Shichao (Journal of Global Economy, Business and Finance, 2025)
As competition in the studio industry intensifies, marketing plays an increasingly important role in studio operations. This paper takes Sanya studio chains as the research object to explore the application and effectiveness of marketing strategies in actual operations. First, the market environment and consumer demand characteristics of Sanya studio chains are analyzed to clarify the positioning of the target customer group. Then, combined with specific cases, the design and implementation of marketing strategies are discussed, including brand building, channel development, service innovation and digital marketing applications. The study shows that accurate market positioning, diversified promotion methods and high-quality customer service are key factors in improving the competitiveness of photo studios. At the same time, as a tourist city, Sanya's wedding photography market has obvious seasonal and tourist-oriented characteristics, and photo studios need to flexibly adjust their marketing strategies according to market changes. Finally, this paper summarizes the experience and challenges in marketing practice, providing valuable reference for the development of the photo studio industry.